Knowledge Affects the Participation of Women of Reproductive Age in the Use of Long-Term Contraceptive Methods - Astuti, Wuri Widi; Soelistyowati, Anik; Ivantarina, Dintya (Jurnal EduHealth, 2022)
The trend of acceptors of family planning in Indonesia so far shows less use of long-term contraceptive methods compared to short-term contraceptive methods. This may be due to limited knowledge or information obtained by women of childbearing age couples, so the aim of this study was to determine the relationship between knowledge and participation of women of childbearing age in the use of long-term contraceptive methods. This type of correlation analytic research was a cross-sectional approach that was carried out in May-2012. June 2022. The research population was all female couples of childbearing age who used active contraception in the Petiken hamlet, Petiken village, Driyorejo Gresik District, totaling 345 women with a total sample of 182 women who met the inclusion criteria through simple random sampling. The data collection method was carried out directly with a research instrument in the form of a questionnaire. Data were analyzed using the Chi-Square statistical test. The results showed that knowledge influenced the participation of women of childbearing age in the use of long-term contraceptive methods (P = 0.000). Knowledge is a very important domain in the formation of one's actions so that a good level of knowledge will determine behavior in the use of long-term contraceptive methods.